Parâmetros morfo-fisiológicos e comportamento agronômico em campo de bananeiras produzidas em biorreator de imersão temporária - (:unkn) unknown (Universidade Federal do Amazonas, 2014)
The objective of this work was to determine morpho-physiological parameters and to determinate the genomic stability of banana plants produced in Temporary Immersion Bioreactor (TIB), besides analyzing the agronomic behavior of the multiplied plant in the field. Therefore, the work was organized in three chapters, as follows: 1- Maintenance, multiplication and acclimatization of banana plants produced in different in vitro cultivation systems; 2- Organogenic behavior and morpho-anatomical characterization of banana plants multiplied in Semi-Solid (SS) and Temporary Immersion Bioreactor (TIB) systems, and; 3 – Cytometric evaluation, morphological and field production of banana plants from plantlets produced in TIB. Initially, banana genotypes were evaluated in vitro under minimal growth conditions, where concentrations of culture medium full and half‐strength MS medium) and two temperatures (20 e 25 °C) were tested. After seven months, the material was evalued and the shoots multiplied in different culture systems, acclimatized. For the multiplication, two systems were evaluated and after, the plants were rooted, then, the plants were acclimatized and evaluated for survival and growthIn all conditions, the plants were evaluated anatomically to better characterize the effects of different treatments and environments on plant development. Finally, at the end of the in vitro propagation process, the plants from TIB were established in the field and evaluated with conventionally produced plants (clump division) during two production cycles. In parallel determinations of nuclear DNA content of the plants were also performed by flow cytometry, , with views to detect possible somaclonal variations of the. It was found that the best maintenance condition of the shoots under in vitro conditions was in full strength MS medium at 20 ºC. After the storage period, the multiplication rates reached values between 1.1 and 2.5 shoots per explant. When SS and TIB systems were compared, It was observed that plants produced in TIB presented higher growth, but, lower multiplication rates than those of the SS system. In general, the in vitro rooting was 100% for both culture systems, and the plant survival in greenhouse reached levels above 70%, with differences between cultivation systems. Morpho-anatomically few differences were observed between plants from TIB or SS systems,, although during acclimatization, increments in the epicuticular wax layer, stomatal density, epidermal thickness and hypodermis in the adaxial face, besides differences between the parenchyma tissues had been characteristic for the plants from both culture systems. Finally, when the plants produced in TIB were evaluated in field, it was found that they presented agronomic behavior similar to those conventionally propagated , without significant changes in nuclear DNA content, neither visual morphological abnormalities that could characterize some type of somaclonal variation. With this work it is possible to conclude that: i) banana plants can be maintained under in vitro minimal growth conditions, before being used for propagating purposes; ii) The TIB provide lower multiplication rates than SS system, althought it can be recommended to be used to lengthen or promote the rooting of shoots in cultivation; iii) Plants produced in TIB present morpho-anatomical characteristics similar to the ones produced in SS system, and; iv) Under field conditions, plantlets produced from TIB have similar agronomic performance to those produzed byconvencional propagation.
Keywords: Micropropagação; Citometria de fluxo; Variação Somaclonal; Desempenho Agronômico; Biorreator de Imersão Temporária (BIT); CIÊNCIAS BIOLÓGICAS